Linguistic and Rhetorical Criticism of Nasser Bukharayi's Poetry - Hosein Ettehadi (مطالعات زبانی و بلاغی)
Some researchers have considered Nasser Bukharayi as a poet of appealing speech, using an eloquent language with selected masterful words. As a poet living in Bukhara in the 8th century AH, he wrote odes and ghazals in the style of Iraqi poets. This research seeks to answer the following question: To what extent are the experts’ opinions about the eloquence and smoothness of his speech correct? Therefore, in the present study, the rhetoric and language of his poetry are examined and analyzed in a descriptive-analytical manner. In the linguistic domain, the results show incorrect use of some combinations and interpretations, catalexis, verbal abstruseness and contradictions in syntactic analogy, causing ambiguity and weakness of his speech. Rhetorically, some far-fetched and unjustifiable congeries among different elements are responsible for conceptual mistakes in the meaning and images of his poetry. In general, much evidence could be found in his poetry, which do not correspond with the standards of eloquence. Nevertheless, the poet’s success in inventing various verb combinations on the one hand and employing familiar phrases and combinations to reflect new meanings on the other hands enabled him to enrich the themes of his speech to some extent.